Drivers' risk perception of roadside trees. Issue 3 (3rd July 2018) - Van Treese, Jeffrey; Koeser, Andrew K.; Fitzpatrick, George E.; Olexa, Michael T.; Allen, Ethan J.
ABSTRACT: Roadside trees can help calm traffic, define roadways, and reduce driver stress. However, roadside trees are also one of the most common components of urban infrastructure involved in single-vehicle crashes. The authors used conjoint analysis to assess driver perceptions of risk associated with roadside trees, road geometry, vehicle speed, and lighting conditions. Florida drivers were shown videos depicting street scenes with randomised variations of these four attributes and were asked to rate their perceived risk. Results indicate that drivers perceived trees in close proximity to roadways as increasing risk and night-time conditions with supplemental lighting as slightly reducing risk. Overall, lighting condition was the most important attribute driving risk ratings, followed (in order of importance) by car speed, tree proximity, and road geometry.